The Use of Busuu Application to Improve First Graders’ Listening Comprehension Achievement - Zovanka Putri Nabila; Nike Angraini; Dio Resta Permana (STIBA IEC JAKARTA, 2024)
This study was designed to know the significant improvement after using busuu application for listening comprehension achievement. It aimed at finding out how applying busuu application could be used to see significant improvement and significant mean difference between the students use busuu application and who did not use busuu application in first graders listening comprehension achievement at SMPN 3 Palembang. This research consisted of two variables, i.e. independent variable (busuu application) and dependent variable (listening comprehension achievement). The research was quantitative method quasi-experimental design. In this study, researcher used especially experimental group and control group. The sample of this research could be 66 students at first graders of SMPN 3 Palembang. After calculating data, the researcher concluded that students' listening can be improve both before and after using the busuu application. The mean results of the pupils' pre-test and post-tests serve as evidence for this. The result showed that there was significant mean difference on students’ listening comprehension because the t-obtained was higher than t-table = (3,966 > 1,997) with sig. (2-tailed) < 0.05 = .000 < 0.05. Which means that the null hypotheses (Ho) was rejected and alternative hypotheses (Ha) was accepted. Moreover, the listening comprehension was significantly improved in the experimental group. The researcher concluded that there was any significant improvement and significant mean difference in the students listening comprehension achievement at SMPN 03 Palembang after being taught using busuu application.